Preparation and Quality Evaluation of Lip Balm Using Aloe Vera Gel - Yanti, Rut Damai; Sulastri, Titin; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
Aloe vera has been used for generations, and its mucilage has been shown to contain 75 beneficial active compounds. This study aimed to formulate and evaluate the physical stability of lip balm preparations containing Aloe vera gel. This study included laboratory experiments with a formulation and evaluation approach to lip balm preparations. Organoleptic evaluation showed that all formulations exhibited a stable semi-solid texture with consistent color and aroma. Homogeneity tests ensured that each preparation was evenly mixed without any coarse particles. All formulations were within the physiological pH range of the skin suitable for topical use. All formulations showed a melting point of 50°C, consistent with the basic characteristics of standard lip balms. Hedonic tests showed varying levels of panelist preference across all formulations in terms of ease of application (F3) (4.2); aroma (F3) (4.3); and physical appearance (F3) (4.2). Overall, the aloe vera gel-based lip balm formulations exhibited good physical stability and acceptable sensory characteristics, indicating their potential to be developed as natural lip care products.